DETERMINATION OF LETHAL CONCENTRATION OF VIBRIO PARAHAEMOLYTICUS AS A POTENTIAL AGENT-CAUSING ACUTE HEPATOPANCREATIC NECROSIS DISEASE (AHPND) IN THE NURSERY STAGE OF WHITE SHRIMP (LITOPENAEUS VANNAMEI) CULTIVATION - Maulana Matin, Hafidh
Whiteleg shrimp (Litopenaeus vannamei) is one of the widely-produced commodities in the aquaculture industry sector in Indonesia due to its high market demand. However, there is a problem of whiteleg shrimp productivity loss caused by the outbreak of acute hepatopancreatic necrosis disease (AHPND) by Vibrio parahaemolyticus at every stage of whiteleg shrimp cultivation, resulting in profit-losses. This study conducted an experiment to determine the lethal concentration of V. parahaemolyticus in whiteleg shrimp to induce AHPND and mortality in whiteleg shrimp at the nursery stage. The nursery of post-larvae PL10 shrimp was done for 28 days, conducted with the same treatment, and grown under optimal growth conditions to obtain optimal whiteleg shrimp. Whiteleg shrimp challenge test against V. parahaemolyticus was done by immersing 10% (v/v) V. parahaemolyticus directly into the tank with various final concentrations of V. parahaemolyticus in the tank, namely 108 CFU/mL, 107 CFU/mL, 106 CFU/mL, 105 CFU/mL, 104 CFU/mL, and 0 (control). During the challenge test, observations of water quality parameters, biological parameters, and microbiological parameters were conducted. The results of the challenge test showed whiteleg shrimp mortality reaching 100% at a concentration 107 CFU/mL of V. parahaemolyticus in the tank within 3 hours after inoculation and at a concentration 108 CFU/mL of V. parahaemolyticus in the tank within 1 hour after inoculation. Observations of shrimp morphology indicated the common AHPND symptoms, such as pale hepatopancreas and empty intestines. Total plate count (TPC) observations on TCBS medium from water samples indicated the presence of colonies potentially to be V. parahaemolyticus proportional to the concentration of V. parahaemolyticus inoculated into the tank. TPC observations on TCBS medium from whole-body shrimp samples indicated the presence of colonies potentially to be V. parahaemolyticus at a density of 106 CFU/mL on dead whiteleg shrimp bodies and showed no presence of microbes with V. parahaemolyticus morphology-like on healthy whiteleg shrimp. From the overall results of the study, it was concluded that the lethal concentration of V. parahaemolyticus in whiteleg shrimp in aquaculture systems due to AHPND is 107 CFU/mL.